f(x)=(x+1)(x-3)(x-3-4i)(x-3+4i)

Simple and best practice solution for f(x)=(x+1)(x-3)(x-3-4i)(x-3+4i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=(x+1)(x-3)(x-3-4i)(x-3+4i) equation:


Simplifying
f(x) = (x + 1)(x + -3)(x + -3 + -4i)(x + -3 + 4i)

Multiply f * x
fx = (x + 1)(x + -3)(x + -3 + -4i)(x + -3 + 4i)

Reorder the terms:
fx = (1 + x)(x + -3)(x + -3 + -4i)(x + -3 + 4i)

Reorder the terms:
fx = (1 + x)(-3 + x)(x + -3 + -4i)(x + -3 + 4i)

Reorder the terms:
fx = (1 + x)(-3 + x)(-3 + -4i + x)(x + -3 + 4i)

Reorder the terms:
fx = (1 + x)(-3 + x)(-3 + -4i + x)(-3 + 4i + x)

Multiply (1 + x) * (-3 + x)
fx = (1(-3 + x) + x(-3 + x))(-3 + -4i + x)(-3 + 4i + x)
fx = ((-3 * 1 + x * 1) + x(-3 + x))(-3 + -4i + x)(-3 + 4i + x)
fx = ((-3 + 1x) + x(-3 + x))(-3 + -4i + x)(-3 + 4i + x)
fx = (-3 + 1x + (-3 * x + x * x))(-3 + -4i + x)(-3 + 4i + x)
fx = (-3 + 1x + (-3x + x2))(-3 + -4i + x)(-3 + 4i + x)

Combine like terms: 1x + -3x = -2x
fx = (-3 + -2x + x2)(-3 + -4i + x)(-3 + 4i + x)

Multiply (-3 + -2x + x2) * (-3 + -4i + x)
fx = (-3(-3 + -4i + x) + -2x * (-3 + -4i + x) + x2(-3 + -4i + x))(-3 + 4i + x)
fx = ((-3 * -3 + -4i * -3 + x * -3) + -2x * (-3 + -4i + x) + x2(-3 + -4i + x))(-3 + 4i + x)
fx = ((9 + 12i + -3x) + -2x * (-3 + -4i + x) + x2(-3 + -4i + x))(-3 + 4i + x)
fx = (9 + 12i + -3x + (-3 * -2x + -4i * -2x + x * -2x) + x2(-3 + -4i + x))(-3 + 4i + x)

Reorder the terms:
fx = (9 + 12i + -3x + (8ix + 6x + -2x2) + x2(-3 + -4i + x))(-3 + 4i + x)
fx = (9 + 12i + -3x + (8ix + 6x + -2x2) + x2(-3 + -4i + x))(-3 + 4i + x)
fx = (9 + 12i + -3x + 8ix + 6x + -2x2 + (-3 * x2 + -4i * x2 + x * x2))(-3 + 4i + x)

Reorder the terms:
fx = (9 + 12i + -3x + 8ix + 6x + -2x2 + (-4ix2 + -3x2 + x3))(-3 + 4i + x)
fx = (9 + 12i + -3x + 8ix + 6x + -2x2 + (-4ix2 + -3x2 + x3))(-3 + 4i + x)

Reorder the terms:
fx = (9 + 12i + 8ix + -4ix2 + -3x + 6x + -2x2 + -3x2 + x3)(-3 + 4i + x)

Combine like terms: -3x + 6x = 3x
fx = (9 + 12i + 8ix + -4ix2 + 3x + -2x2 + -3x2 + x3)(-3 + 4i + x)

Combine like terms: -2x2 + -3x2 = -5x2
fx = (9 + 12i + 8ix + -4ix2 + 3x + -5x2 + x3)(-3 + 4i + x)

Multiply (9 + 12i + 8ix + -4ix2 + 3x + -5x2 + x3) * (-3 + 4i + x)
fx = (9(-3 + 4i + x) + 12i * (-3 + 4i + x) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = ((-3 * 9 + 4i * 9 + x * 9) + 12i * (-3 + 4i + x) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = ((-27 + 36i + 9x) + 12i * (-3 + 4i + x) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + (-3 * 12i + 4i * 12i + x * 12i) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))

Reorder the terms:
fx = (-27 + 36i + 9x + (-36i + 12ix + 48i2) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + (-36i + 12ix + 48i2) + 8ix * (-3 + 4i + x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + (-3 * 8ix + 4i * 8ix + x * 8ix) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))

Reorder the terms:
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + (-24ix + 8ix2 + 32i2x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + (-24ix + 8ix2 + 32i2x) + -4ix2 * (-3 + 4i + x) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + (-3 * -4ix2 + 4i * -4ix2 + x * -4ix2) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))

Reorder the terms:
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + (12ix2 + -4ix3 + -16i2x2) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + (12ix2 + -4ix3 + -16i2x2) + 3x * (-3 + 4i + x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + (-3 * 3x + 4i * 3x + x * 3x) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))

Reorder the terms:
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + (12ix + -9x + 3x2) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + (12ix + -9x + 3x2) + -5x2 * (-3 + 4i + x) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + (-3 * -5x2 + 4i * -5x2 + x * -5x2) + x3(-3 + 4i + x))

Reorder the terms:
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + (-20ix2 + 15x2 + -5x3) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + (-20ix2 + 15x2 + -5x3) + x3(-3 + 4i + x))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + -20ix2 + 15x2 + -5x3 + (-3 * x3 + 4i * x3 + x * x3))

Reorder the terms:
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + -20ix2 + 15x2 + -5x3 + (4ix3 + -3x3 + x4))
fx = (-27 + 36i + 9x + -36i + 12ix + 48i2 + -24ix + 8ix2 + 32i2x + 12ix2 + -4ix3 + -16i2x2 + 12ix + -9x + 3x2 + -20ix2 + 15x2 + -5x3 + (4ix3 + -3x3 + x4))

Reorder the terms:
fx = (-27 + 36i + -36i + 12ix + -24ix + 12ix + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 36i + -36i = 0
fx = (-27 + 0 + 12ix + -24ix + 12ix + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)
fx = (-27 + 12ix + -24ix + 12ix + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 12ix + -24ix = -12ix
fx = (-27 + -12ix + 12ix + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: -12ix + 12ix = 0
fx = (-27 + 0 + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)
fx = (-27 + 8ix2 + 12ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 8ix2 + 12ix2 = 20ix2
fx = (-27 + 20ix2 + -20ix2 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 20ix2 + -20ix2 = 0
fx = (-27 + 0 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)
fx = (-27 + -4ix3 + 4ix3 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: -4ix3 + 4ix3 = 0
fx = (-27 + 0 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)
fx = (-27 + 48i2 + 32i2x + -16i2x2 + 9x + -9x + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 9x + -9x = 0
fx = (-27 + 48i2 + 32i2x + -16i2x2 + 0 + 3x2 + 15x2 + -5x3 + -3x3 + x4)
fx = (-27 + 48i2 + 32i2x + -16i2x2 + 3x2 + 15x2 + -5x3 + -3x3 + x4)

Combine like terms: 3x2 + 15x2 = 18x2
fx = (-27 + 48i2 + 32i2x + -16i2x2 + 18x2 + -5x3 + -3x3 + x4)

Combine like terms: -5x3 + -3x3 = -8x3
fx = (-27 + 48i2 + 32i2x + -16i2x2 + 18x2 + -8x3 + x4)

Solving
fx = -27 + 48i2 + 32i2x + -16i2x2 + 18x2 + -8x3 + x4

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = -27x-1 + 48i2x-1 + 32i2 + -16i2x + 18x + -8x2 + x3

Simplifying
f = -27x-1 + 48i2x-1 + 32i2 + -16i2x + 18x + -8x2 + x3

Reorder the terms:
f = 32i2 + 48i2x-1 + -16i2x + -27x-1 + 18x + -8x2 + x3

See similar equations:

| -2v^2+3v-1=0 | | (9t+5)=10*6t | | 5-6d=-9 | | 3td=12t | | 0.2(n-3.2)=3 | | 12-x+4x^2-9x^7=0 | | 3(3x)+2(5)=6x-500 | | 3(x+2.2)=13.5 | | X-8=6-x | | -x+4=3x+2x-8 | | 7(-17)2-6(-17)=-27+12 | | -5x^2+24x+36=0 | | 18-3x=-8x+13 | | 2xsquared-11x=-15 | | -4x-1=-7x-4 | | 7c+2-6c=-27+12 | | 0.20y+24+15=46 | | 4x^2+4y^2-24=0 | | 4x^2+4y^2=24 | | (8x^2/3)^3= | | -4b-2=2b-2b | | 5x-4(x-7)=34 | | -7x+32=21 | | 4(y+3)=y+24 | | 2m+20=3m+8 | | 3r-1+r=2(1-2r) | | C+1.89=3.9 | | (8x^2/3)^3 | | Log(9x-8)=3 | | 0.66666666666(1+n)=-0.5n | | k+7=3+k+4 | | -3/4×17/3 |

Equations solver categories